Relations of Food Pattern and Physical Activity with Academic Achievement and Cognitive Function - Wulandari, Ayu; Lubis, Zulhaida; Aritonang, Evawani (Green Medical Journal, 2020)
Introduction: The results of the initial survey showed that there were seven children with low food pattern and moderate physical activity was having a cognitive function and low academic achievement at school, and three children with good food pattern and moderate physical activity were having good cognitive and high academic achievement in school. This study was to determine the relations of food patterns and physical activity with academic achievement and cognitive function. Methods: This study was a cross-sectional study that was conducted at Elementary School 2 Blangkeujeren, West Labuhanhaji Sub-district, South Aceh District from March 2017 to June 2017. This study used a total sampling design is 81 students. Subjects are all students in grade five (42 students) and six (39 students). Data were collected by using questionnaires include Food Frequency Questionary (FFQ), Food Recall 24 hours, Physical Activity Level (PAL). Last year's report card value and the Mini-Mental State Examination (MMSE) were used to assess cognitive children. Results: The relationship between the type and the amount of macro and micronutrient intake obtained p-value<0.05. This study also showed a relationship between food patterns and cognitive function in children. Based on the research results, there is a relationship between physical activity and academic achievement (p<0.05). There is a relationship between physical activity and cognitive function in children. Conclusion: There is a relationship between food patterns, physical activity, academic achievement, and cognitive function.